Neuroprotective effects of mGluR5 activation through the PI3K/Akt pathway and the molecular switch of AMPA receptors. (1st January 2020) - Cavallo, Damiana; Landucci, Elisa; Gerace, Elisabetta; Lana, Daniele; Ugolini, Filippo; Henley, Jeremy M.; Giovannini, Maria Grazia; Pellegrini-Giampietro, Domenico E.
Abstract: Previous studies have demonstrated that antagonists of mGluR1, but not mGluR5, are neuroprotective in models of cerebral ischemia. To investigate the individual roles of mGlu1 and mGlu5 receptors in in vitro model of cerebral ischemia we used low doses of the non-selective group I agonist DHPG and mGlu1 and mGlu5 selective positive allosteric modulators (PAMs). In hippocampal slices subjected to 30 min oxygen-glucose deprivation (OGD), DHPG (1 μM) and the mGluR5 PAM (VU0092273) significantly reduced OGD-induced CA1 injury monitored by propidium iodide staining of the slices and quantitative analysis of CA1 neurons. In contrast, the mGluR1 PAM (VU0483605) showed no neuroprotection. These protective effects of DHPG and VU0092273 were prevented by inhibition of PI3K/Akt pathway by LY294002. The mGluR5 PAM (VU0092273) also prevented GluA2 down-regulation triggered by ischemic injury, via PI3K/Akt pathway, revealing a further contribution to its neuroprotective effects by reducing the excitotoxic effects of increased Ca 2+ influx through GluA2-lacking AMPA receptors. Furthermore, immunohistochemical assays confirmed the neuroprotective effect of VU0092273 and revealed activation of glia, indicating the involvement reactive astrogliosis in the mechanisms of neuroprotection. Our data suggest that selective activation/potentiation of mGluR5 signalling represents a promising strategy for the development of new interventions to reduce or prevent ischemia-induced neuronal death. Highlights: mGluR5 activation with DHPG and VU0092273 showed neuroprotective effects in OGD. mGluR5 exerted its neuroprotective effects via PI3K/Akt pathway. mGluR5 also prevented the GluA2 down-regulation following an ischemic injury. mGluR5 appears to stimulate neuroprotective responses in astrocytes and microglia.